2014
DOI: 10.1039/c4cp00808a
|View full text |Cite
|
Sign up to set email alerts
|

Water and small organic molecules as probes for geometric confinement in well-ordered mesoporous carbon materials

Abstract: Mesoporous carbon materials were synthesized employing polymers and silica gels as structure directing templates. The basic physico-chemical properties of the synthetic mesoporous materials were characterized by (1)H and (13)C MAS solid-state NMR, X-ray diffraction, transmission electron microscopy (TEM) and nitrogen adsorption measurements. The confinement effects on small guest molecules such as water, benzene and pyridine and their interactions with the pore surface were probed by a combination of variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 78 publications
3
38
0
Order By: Relevance
“…Two spectral features are clearly visible for the TFSI anions, with the broad feature at −84.9 ppm assigned to adsorbed anions nearby carbon surfaces within the carbon micropores (referred to as in-pore) and the narrow feature at −78.3 ppm assigned to nonadsorbed anions occupying large reservoirs of ionic liquid between primary carbon particles (referred to as ex-pore). 38 41 As discussed in the Introduction , the in-pore feature is shifted relative to the ex-pore due to the local magnetic field arising from the circulation of delocalized π electrons in the carbon. The ex-pore anions on the other hand are remote from carbon surfaces and therefore have a chemical shift that is essentially identical to the neat ionic liquid (−78.3 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two spectral features are clearly visible for the TFSI anions, with the broad feature at −84.9 ppm assigned to adsorbed anions nearby carbon surfaces within the carbon micropores (referred to as in-pore) and the narrow feature at −78.3 ppm assigned to nonadsorbed anions occupying large reservoirs of ionic liquid between primary carbon particles (referred to as ex-pore). 38 41 As discussed in the Introduction , the in-pore feature is shifted relative to the ex-pore due to the local magnetic field arising from the circulation of delocalized π electrons in the carbon. The ex-pore anions on the other hand are remote from carbon surfaces and therefore have a chemical shift that is essentially identical to the neat ionic liquid (−78.3 ppm).…”
Section: Resultsmentioning
confidence: 99%
“… 38 40 Density functional theory (DFT) calculations of nucleus-independent chemical shifts (NICSs) nearby various sp 2 -hybridized carbon structures have offered insights into the experimentally observed spectra and suggest that the shifts observed for adsorbed species depend primarily on the structure of the carbon adsorbent. 38 , 41 44 NMR experiments on typical activated carbons soaked with organic electrolytes have shown that the carbon micropores are wetted in the absence of an applied potential, i.e., they may be considered as ionophilic. 38 , 39 , 45 , 46 Both in situ 47 , 48 and ex situ 49 NMR studies of supercapacitors with organic electrolytes have shown that the populations of anions and cations inside the carbon micropores change when a voltage is applied and that the exact charge storage mechanism is sensitive to the electrolytes used and their concentration.…”
Section: Introductionmentioning
confidence: 99%
“…28 Moreover, nanoporous carbons are known to be highly disordered: they present a range of pore sizes and geometries, as well as features such as five-membered rings, sheet edges, and curved sheets. 32,33 DFT calculations have shown that curvature 8 and the presence of sheet edges 34 have a large effect on the local magnetic field and thus on the chemical shifts. The variety of local structures will thus lead to a large range of chemical shifts for adsorbates and may affect the observed lineshapes.…”
Section: Variation Of the Average Chemical Shift As A Function Of mentioning
confidence: 99%
“…For the three VOCs, higher amounts were associated with an enlargement towards high ppm values, which induced a shift of approximately 1 ppm of the MAS averaged signal. This phenomenon was already obtained on mesoporous and microporous carbons 32,24 . Thirdly, for increasing loadings of VOCs, the initial adsorbed water signal vanished while a new peak located a few ppm away appeared.…”
Section: Magnetic Inhomogeneities (Distribution Effects)mentioning
confidence: 82%
“…Such a signal can be generated by a part of the adsorbed molecules exhibiting large dipolar coupling 31,32 . For this specific purpose, high field 1 H NMR recordings correlated with very high MAS frequencies were carried out with the aim of detecting such interaction effects.…”
Section: Anisotropy Effectsmentioning
confidence: 99%